PATH-19. TUMOR HETEROGENEITY IN GLIOMAS: A PILOT STUDY OF HISTOPATHOLOGY-ASSOCIATED PROTEOME PROFILES ASSESSED BY LIQUID CHROMATOGRAPHY TANDEM MASS SPECTROMETRY OF FFPE SAMPLES. (11th November 2019) - Paixao Becker, Aline; Hlavin Bell, Erica; Jaharul Haque, S; McElroy, Joseph; Fleming, Jessica; Han, Chunhua; Popp, Illinca; Prinz, Marco; Staszewski, Ori; Grosu, Anca; Chakravarti, Arnab
Abstract: Herein, we aimed to scrutinize tumor heterogeneity of infiltrative gliomas based on histopathological phenotypes, through proteomic profiling of formalin-fixed, paraffin embedded (FFPE) tissue. FFPE tissues are promising samples for proteomic studies, which can support the elucidation of glioma evolution and identify therapeutically vulnerable proteins and signaling pathways that drive recurrence and resistance mechanisms. We represented 2–3 adjacent, phenotypically distinct areas from 12 grade II-IV gliomas diagnosed according to the 2016 WHO classification, in a total of 35 samples (1.0mm cores), that were analyzed employing liquid chromatography tandem mass spectrometry (LC-MS/MS) for label-free expression proteomics. The statistical analysis was performed using R and Qlucore™ omics explorer software. Overall, 9222 peptides were mapped to 1758 non-redundant proteins, 320 of which had a significant (p< 0.05) differential expression in glioblastomas versus lower grade gliomas (Wilcoxon test comparing average expression). Principal component analysis (PCA) of the whole set of proteins showed clustering of the samples by tumor grade and IDH status. Unsupervised hierarchical analysis of the most significantly expressed proteins (p= 0.01, FDR= 0.05) showed that IDH wt gliomas had high expression of proteins related to cell movement, DNA structure, and fatty acid metabolism throughout the samples. IDH mut gliomas largely displayed high expression of mitochondrial enzymes related to energy production and neurotransmitter metabolism, with subsets closely related to 1p19q status and histological grade. Importantly, we demonstrated that LC-MS/MS analysis of FFPE core samples is feasible and enables recognition of different proteome signatures across histopathological phenotypes within a single tumor. This is the first study, to our knowledge, exploring proteome profiles addressing histopathological heterogeneity in gliomas by LC-MS/MS analysis of FFPE samples, which warrants further validation in independent datasets including ones that utilize frozen specimens. FUNDING: R01CA108633, R01CA169368, RC2CA148190, U10CA180850-01 (NCI), Brain Tumor Funders Collaborative Grant, and the Ohio State University CCC (all to AC).